Experimental and theoretical exploration of mechanical stability of Pt/NbO2 interfaces for thermoelectric applications. (23rd October 2017) - Music, Denis; Schmidt, Paul; Saksena, Aparna
Abstract: Mechanical stability criteria for metallic contacts, namely a minimised thermal stress and an enhanced interfacial strength, have been appraised for sputtered, x-ray amorphous NbO2 thermoelectric thin films in contact with a polycrystalline Pt electrode utilising experimental and theoretical methods. Thermal stress built at these Pt/NbO2 interfaces with approximately 50 MPa is minute even at 800 °C, the maximum operation temperature. There are no coordination changes of Pt and its metallic character is only marginally altered upon the interface formation. In addition, Nb–O bonds at the interface sustain their covalent-ionic dioxide bonding nature. Hence, even though there are no considerable modifications in the electronic structure of the individual components at these interfaces, Pt/NbO2 interfacial bonds of metallic and partly covalent character are strong with a work of separation reaching 2 J m −2 . Based on the synergic experimental and theoretical results, it is therefore expected that these interfaces are mechanically stable during operation of these thermoelectric devices. This strategy is of general importance for designing mechanically stable electrical contacts.